Nanozyme-assisted amplification-free CRISPR/Cas system realizes visual detection - Zhang, Yuan; Yu, Wanpeng; Wang, Man; Zhang, Lei; Li, Peifeng (Frontiers in Bioengineering and Biotechnology, 2024)
The CRISPR (clustered regularly interspaced short palindromic repeats)/Cas (CRISPR associated) system has proven to be a powerful tool for nucleic acid detection due to its inherent advantages of effective nucleic acid identification and editing capabilities, and is therefore known as the next generation of molecular diagnostic technology. However, the detection technologies based on CRISPR/Cas systems require preamplification of target analytes; that is, target gene amplification steps through isothermal amplification or PCR before detection to increase target analyte concentrations. This creates a number of testing limitations, such as extended testing time and the need for more sophisticated testing instruments. To overcome the above limitations, various amplification-free assay strategies based on CRISPR/Cas systems have been explored as alternatives, which omit the preamplification step to increase the concentrations of the target analytes. Nanozymes play a pivotal role in enhancing the sensitivity of CRISPR-based detection, enabling visual and rapid CRISPR assays. The utilization of nanozyme exceptional enzyme-like catalytic activity holds great promise for signal amplification in both electrochemical and optical domains, encompassing strategies for electrochemical signal sensors and colorimetric signal sensors. Rather than relying on converting a single detection target analyte into multiple analytes, these methods focus on signal amplification, the main mechanism of which involves the ability to form a large number of reporter molecules or to improve the performance of the sensor. This exploitation of nanozymes for signal amplification results in the heightened sensitivity and accuracy of detection outcomes. In addition to the strategies that improve sensor performance through the application of nanozymes, additional methods are needed to achieve visual signal amplification strategies without preamplification processes. Herein, we review the strategies for improving CRISPR/Cas systems that do not require preamplification, providing a simple, intuitive and preamplification-free CRISPR/Cas system detection platform by improving in-system one-step amplification programs, or enhancing nanozyme-mediated signal amplification strategies.